REVIEW ARTIKEL : TELAAH PENGOBATAN MODERN GOLONGAN DIURETIK DENGAN TANAMAN HERBALNYA - Indah Sari Amanatun Nisa Indah; Eko Sri Wahyuningsih; Neni Sri Gunarti (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2023)
Hypertension is one of the most common diseases in adults and a risk factor for cardiovascular disease. Hypertension can be said to be a